PENGEMBANGAN MODEL PEMBELAJARAN PBL DALAM UPAYA MENINGKATKAN KEMAMPUAN BERPIKIR HOTS MAHASISWA - Popon Mariam; Cucu Lisnawati (SOSIOHUMANITAS, 2020)
The research entitled Development of the PBL Learning Model in an effort Improving Student HOTS Ability is carried out as a demand of students’ requirement in developing higher order thinking skills (HOTS). The research method uses the Research and Development method from Borg and Gall. The development stages include: 1. research and data collection; 2. planning; 3. product development; and 4. validation and trial. The research results based on the limited and extensive trials show that: 1) the developed PBL model is suitable for use, 2) the final product from the PBL learning model development is very effective to improve students' HOTS. Conclusion shows that the final product of the PBL learning model development is feasible and effective on increasing students' HOTS. The output target of technological readiness in this research is to improve students' HOTS abilities and the publication on accredited national journal.